The regional network on AIDS, livelihoods, and food security (RENEWAL): Influencing change in HIV/AIDS policy through networks - Frankenberger, Timothy R.; Nelson, Suzanne; TANGO International, Inc. (International Food Policy Research Institute, 2013)
As the magnitude and scope of the AIDS epidemic grew during the 1990s, it transformed the international development landscape: HIV/AIDS became a global development issue with socioeconomic implications for livelihoods, rather than an isolated health issue. Sub-Saharan Africa remains the most HIV-affected region in the world: an estimated 22.4 million people live with HIV in Sub-Saharan Africa. In response to this crisis, the Regional Network on AIDS, Livelihoods, and Food Security (RENEWAL) was officially launched in 2001 as a joint project of the International Food Policy Research Institute (IFPRI) and the International Service for National Agricultural Research (ISNAR), and was operational in Malawi, Uganda, Kenya, Zambia, and South Africa through most of 2011.